Therapeutic Targeting of Epigenetic Components in Amyotrophic Lateral Sclerosis (ALS) - Lee, J.; Ryu, H.; Keum, G.; Yoon, Y.J.; Kowall, N.W.; Ryu, H. (Current Medicinal Chemistry, 2014)
Amyotrophic lateral sclerosis (ALS) is an adult-onset motor neuron disease characterized by degeneration of motor neuron and glial activation followed by the progressive muscle loss and paralysis. Numerous distinct therapeutic interventions have been examined but currently ALS does not have a cure or an efficacious treatment for the disorder. Glutamate- induced excitotoxicity, inflammation, mitochondrial dysfunction, oxidative stress, protein aggregation, transcription deregulation, and epigenetic modifications are associated with the pathogenesis of ALS and known to be therapeutic targets in ALS. In this review, we discuss translational pharmacological studies targeting epigenetic components to ameliorate ALS. Understanding of the epigenetic mechanisms will provide novel insights that will further identify potential biological markers and therapeutic approaches for treating ALS. A combination of treatments that modulate epigenetic components and multiple targets may prove to be the most effective therapy for ALS.
Keywords: therapeutics